Impact of Professional Development Program on Pedagogical Competence of Teachers at MI Az Zahro' Pagar Alam - Rita Yulia Anggraini; Muhammad Uyun (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The goals of this research are to provide a historical context for the evolution of the teaching profession, to characterize the current state of teacher performance, and to identify the factors that have an impact on teachers' professional effectiveness. This study focuses on the professional growth of experienced instructors, although previous research has mostly ignored this topic. A survey strategy is used. In order to gather information for this study, researchers filled out questionnaires. Twenty-one teachers from MI Az Zahro’ Pagar Alam were interviewed for this study. Simple regression was used to evaluate the data. The findings demonstrated that (1) teacher professional development is at an acceptable level, and (2) professional development has a beneficial effect on teacher performance.